Why double‐kissing crush should be preferred over culotte for two‐stent bifurcation stenting. Issue 7 (8th June 2022) - Simsek, Bahadir; Brilakis, Emmanouil S.
Key points: The thrombogenicity of the double‐kissing (DK) crush and culotte bifurcation stenting techniques was assessed with three different stent types using optical coherence tomography in a porcine arteriovenous shunt model. Culotte had malapposition in the proximal main vessel, which was not observed in DK crush. Culotte also had more thrombus in the bifurcation area compared with DK crush. DK crush may be preferable to culotte when performing bifurcation stenting using an upfront two‐stent strategy.